A Model of U.K. Emigration, 1870-1913 - Hatton, Timothy J. (The Review of Economics and Statistics, 1995)
This paper develops a simple time series model of emigration and applies it to data for emigration from the UK, 1870-1913. The model is derived from a microeconomic analysis of the migration decision and provides a specific functional form and dynamic structure. It encompasses and explains many of the empirical findings of earlier research on the determinants of emigration over this historical period. The results support the model strongly in most respects. Both wage rates and employment rates in the sending and in the receiving countries influenced fluctuations in emigration. The short-run fluctuations were driven largely by variations in employment rates while the long-run level of emigration was determined largely by the relative wage. -Author